2021
DOI: 10.18632/aging.203722
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and immune infiltration signatures of proteasome 26S subunit, non-ATPase (PSMD) family genes in breast cancer patients

Abstract: The complexity of breast cancer includes many interacting biological processes that make it difficult to find appropriate therapeutic treatments. Therefore, identifying potential diagnostic and prognostic biomarkers is urgently needed. Previous studies demonstrated that 26S proteasome delta subunit, non-ATPase (PSMD) family members significantly contribute to the degradation of damaged, misfolded, abnormal, and foreign proteins. However, transcriptional expressions of PSMD family genes in breast cancer still r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…Furthermore, we also observed several genes belonging to Histone H1 axis, known to be a therapeutic target in cancer cell self-renewal [49] . Interestingly, in etoposide resistant clusters we found numerous genes belonging to PSMB , PSMC , and PSMD proteasome-subunit families, known to confer drug resistance in diverse cancers [50] , [51] , [52] .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, we also observed several genes belonging to Histone H1 axis, known to be a therapeutic target in cancer cell self-renewal [49] . Interestingly, in etoposide resistant clusters we found numerous genes belonging to PSMB , PSMC , and PSMD proteasome-subunit families, known to confer drug resistance in diverse cancers [50] , [51] , [52] .…”
Section: Discussionmentioning
confidence: 97%
“…The findings indicate that compared with high immune cell infiltration, patients with low immune cell infiltration levels may appear poor outcomes to conventional therapy in some solid tumors ( Tobin et al, 2019 ). A paper from reported that the expression of PSMD member genes including PSMD2 is related to markers of six tumor-infiltrating immune cell types in breast cancer Xuan et al (2021) . In this study, we analyzed the correlation between the expression of PSMD2 and immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of lung cancer patients enrolled in this study was relatively small. Moreover, PSMD family genes are reported to correlate with immune infiltration profiles in breast cancer ( Xuan et al, 2021 ). Up to now, there is no studies have designed to investigate the association between PSMD2 expression and immune cell infiltration in lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…We identified 208 proteins differentially enriched in the aging cortex ( Figure 4A ) and showed that 79% of these proteins (164/208) were involved in catabolic and metabolic processes such as the proteasome complex ( Figure 4C ). PSMD and PSMC proteins, which are proteasome 26S subunits involved in the degradation of misfolded and abnormal proteins (Kao et al 2021; Xuan et al 2021), were specifically enriched in this subset ( Supplemental Table 1 ). It was reported that damaged and misfolded proteins tend to accumulate during the brain aging process, and that the proteasome is responsible for the degradation of these proteins (Carrard et al 2002; Keller, Gee, and Ding 2002; Saez and Vilchez 2014).…”
Section: Discussionmentioning
confidence: 99%